Sticky Platelet Syndrome as a Cause of Recurrent Miscarriages: A Rare Case Report - Dedy Kristofer Simangunsong; Alvina Widhani; Ardhi Rahman Ahani; Eirene Simbolon; Hadiki Habib (Acta Medica Indonesiana)
Sticky platelet syndrome (SPS) is a hereditary disorder. SPS can cause pregnancy complications, such as recurrent miscarriages. However, proper management can prevent the incidence of recurrent miscarriages. Here, we describe a case of a woman who lost her fifth first-trimester pregnancy, and upon assessment, we discovered SPS. The 33-year-old woman underwent consultation with an obstetrician because of her history of five first-semester miscarriages. Gynecology ultrasound, infection parameters, hormonal and metabolic panels, and autoimmune workup were all found to be normal; however, vitamin D deficiency was identified as was SPS from a platelet aggregation test. The patient was then treated with clopidogrel and vitamin D3 supplementation. She became pregnant after five months of treatment. Her pregnancy was normal and she went into delivery at 40 weeks gestation with no maternal or fetal complications.